The association between cigarette smoking and health care service utilization among middle-aged and elderly adults in China - Song, Jiarui; Jin, Chenggang; Cheng, Xi (Frontiers in Public Health, 2022)
Objective To assess the associations between tobacco use and health care service utilization in Chinese individuals aged more or equal to 40 years old. Method This research was a cross-sectional study using data from eight provinces in China, and the final sample consisted of 4,733 observations (4,749 participants) aged more or equal to 40 years old. The dependent variable was health care utilization measured by outpatient and inpatient service utilization. Descriptive statistics were used to summarize the socio-demographic characteristics of the sample according to smoking status. The association between tobacco use and health care service utilization was examined by an instrumental variable (IV) probit model. Results Of the respondents interviewed in 2020, 3,116 (65.84%) were never smokers, 654 (13.82%) were smokers with the smoking index (SI) <400, and 963(20.34%) were smokers with SI≥400. Smokers with SI <400 reported a 6.80% higher probability of using outpatient services. Smokers with SI <400 and SI≥400 reported a 3.10 and 4.20% higher average probability of using ≥3 outpatient visits than never smokers, respectively. Additionally, smokers with SI <400 and SI≥400 reported a 6.30 and 6.20% higher average probability of using inpatient services than those who had not smoked. Moreover, smokers with SI≥400 were more likely to have had ≥2 hospital visits than nonsmokers. Conclusions Smokers make greater use of health care services. Control of smoking may ease the burden of related health care utilization.